Effects of intranasal oxytocin administration on memory for infant cues: Moderation by childhood emotional maltreatment - Bhandari, R; van der Veen, R; Parsons, C; Young, K; Voorthuis, A; Bakermans-Kranenburg, M; Stein, A; Kringelbach, M; van IJzendoorn, M (Psychology Press Ltd, 2014)
Oxytocin has been implicated in parent-infant attachment and social recognition. With respect to emotion recognition memory, both memory-enhancing and impairing effects have been observed, suggesting an influence of individual factors. We assessed the effects of oxytocin on memory for infant cues, and whether these effects are moderated by self-reported childhood emotional maltreatment. Nulliparous females (N = 102) participated in a randomized, double-blind, between-subjects study with intranasal oxytocin or placebo administration. Participants' memory was tested using the Baby Social Reward Task, where participants were asked to select the happier infant from a pair of two infants based on the information that they received about the infants' mood in the previous phase. Participants reporting more childhood emotional maltreatment were less accurate in this task after inhaling oxytocin. Our findings add to a growing body of literature showing that the effects of intranasal oxytocin on memory and social behavior are moderated by adverse early life experiences. © 2014 Taylor and Francis.